2019
DOI: 10.3390/ijms20071706
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Nrf2- and ATF4-Activation by Carnosic Acid Cooperatively Induces Expression of Cytoprotective Genes

Abstract: : Carnosic acid (CA) is a phytochemical found in some dietary herbs, such as Rosmarinus officinalis L., and possesses antioxidative and anti-microbial properties. We previously demonstrated that CA functions as an activator of nuclear factor, erythroid 2 (NF-E2)-related factor 2 (Nrf2), an oxidative stress-responsive transcription factor in human and rodent cells. CA enhances the expression of nerve growth factor (NGF) and antioxidant genes, such as HO-1 in an Nrf2-dependent manner in U373MG human astrocytoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…In addition, we recently identified several antioxidant and cytoprotective genes including nerve growth facts (NGF) are cooperatively regulated by both Nrf2 and ATF4 when both are activated by the phytochemical carnosic acid in the human glioma U373MG cells [124]. Interestingly, genes involved in glutathione synthesis are regulated to various extent in either an Nrf2 and ATF4-dependent or in a both Nrf2-and ATF4-dependent manner ( Figure 6) ( [124] and our unpublished observation). Furthermore, genes involved in NADPH synthesis in the mitochondria such as SHMT2 and MTHFD2 are regulated by ATF4 [29] and those in the cytosol (i.e.…”
Section: Nrf2 and Atf4 Crosstalk In Mitochondrial Retrograde Signalingmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, we recently identified several antioxidant and cytoprotective genes including nerve growth facts (NGF) are cooperatively regulated by both Nrf2 and ATF4 when both are activated by the phytochemical carnosic acid in the human glioma U373MG cells [124]. Interestingly, genes involved in glutathione synthesis are regulated to various extent in either an Nrf2 and ATF4-dependent or in a both Nrf2-and ATF4-dependent manner ( Figure 6) ( [124] and our unpublished observation). Furthermore, genes involved in NADPH synthesis in the mitochondria such as SHMT2 and MTHFD2 are regulated by ATF4 [29] and those in the cytosol (i.e.…”
Section: Nrf2 and Atf4 Crosstalk In Mitochondrial Retrograde Signalingmentioning
confidence: 85%
“…We have also reported that proteasome inhibitors activate both Nrf2 and ATF4 and cooperatively induce the expression of the cystine transporter xCT in bladder cancer cells via Nrf2 binding to ARE and ATF4 binding to amino acid response elements (AAREs), respectively [123]. In addition, we recently identified several antioxidant and cytoprotective genes including nerve growth facts (NGF) are cooperatively regulated by both Nrf2 and ATF4 when both are activated by the phytochemical carnosic acid in the human glioma U373MG cells [124]. Interestingly, genes involved in glutathione synthesis are regulated to various extent in either an Nrf2 and ATF4-dependent or in a both Nrf2-and ATF4-dependent manner ( Figure 6) ( [124] and our unpublished observation).…”
Section: Nrf2 and Atf4 Crosstalk In Mitochondrial Retrograde Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the sustained activation of PI3K-AKT pathway inhibits GSK3, which phosphorylates NRF2 and allows its recognition and ubiquitination by βTrCP-CUL1 ubiquitin E3 ligase for degradation. As for another cooperative factor, ATF4 activation has a synergistic effect with NRF2 activation on xCT expression (Ye et al 2014;Mimura et al 2019). Consequently, cystine uptake coupled with glutamate excretion and glutathione synthesis are enhanced (Fig.…”
Section: Potent Antioxidant Function At the Expense Of Central Carbonmentioning
confidence: 99%
“…It is likely that capsaicin indirectly activates some cellular antioxidant mechanisms, but it may not function well in zebrafish larvae. Carnosic acid has been reported to exhibit antioxidant activity through the Nrf2 pathway in various cells and mice [31,52]. However, in zebrafish larvae, the toxicity of carnosic acid was so strong that we could not analyze it at concentrations ≥5 µM, and even at 1 µM, the numbers of surviving larvae were significantly decreased due to cotoxicity when they were further treated with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 94%